Analisis Yuridis Peran Informed Consent dalam Penghapusan Pertanggungjawaban Pidana bagi Tenaga Medis - Utari Sastrani , I Dewa Ayu Nyoman (CV. Era Digital Nusantara, 2025)
This research analyzes the juridical role of informed consent in eliminating criminal liability for medical professionals in Indonesia. Through a normative-juridical approach with descriptive-qualitative analysis methods, this study examines the legal framework of informed consent and its function as grounds for eliminating criminal liability. Informed consent gains normative legitimacy through various legislation, including Law Number 36 of 2009 on Health and Minister of Health Regulation Number 290/Menkes/Per/III/2008 on Medical Treatment Consent. The results reveal that valid informed consent can be constructed as a justification that eliminates the